Analysis of sensitive skin barrier function: basic indicators and sebum composition. (5th January 2018) - Fan, L.; Jia, Y.; Cui, L.; Li, X.; He, C.
Abstract: Objectives: Sensitive skin (SS) is a condition characterised by high reactivity, low tolerance, and susceptibility to allergies of the skin. Owing to changes in the environment and marketing strategies, as well as the increasing public awareness about skin care, attention to skin condition is gradually increasing. The aim of this study is to explore the differences in the skin barrier of SS and normal skin (NS). Methods: A questionnaire survey was conducted and basic indicators of the skin barrier were analysed. It was found that sebum secretion in the SS group was lower than that in the NS group, suggesting that the development of SS might be associated with sebum secretion and its specific components. Next, an ultra performance liquid chromatography‐quadruple time‐of‐flight mass spectrometer was used to identify facial sebum components in female volunteers. Results: The results showed that the sebum of female volunteers with SS had high levels of ceramides, glycerophosphoethanolamines, and diacylglycerols, and low levels of glucosylceramides, glycerophosphoserines, glycerophosphocholines, and triacylglycerols. Conclusion: Analysis of lipid functions suggested that the main reason for SS development in women might be a barrier dysfunction caused by excessive apoptosis and lack of water. Therefore, anti‐allergy additives in cosmetic products that could inhibit apoptosis of keratinocytes and methods to maintain the stability of water molecules in the skin should be further studied. Abstract : Sebum components are different between sensitive skin and normal skin.